An environmental framework for informal settlements to achieve sustainable sanitation management : the case of the Democratic Resettlement Community (DRC), Swakopmund, Namibia - Rosalia, Neshuku (Stellenbosch : Stellenbosch University, 2024)
Thesis (MPhil)--Stellenbosch University, 2024.